Digital particle image velocimetry measurements of the downwash distribution of a desert locust Schistocerca gregaria. - Bomphrey, R; Taylor, G; Lawson, N; Thomas, A (2006)
Actuator disc models of insect flight are concerned solely with the rate of momentum transfer to the air that passes through the disc. These simple models assume that an even pressure is applied across the disc, resulting in a uniform downwash distribution. However, a correction factor, k, is often included to correct for the difference in efficiency between the assumed even downwash distribution, and the real downwash distribution. In the absence of any empirical measurements of the downwash distribution behind a real insect, the values of k used in the literature have been necessarily speculative. Direct measurement of this efficiency factor is now possible, and could be used to compare the relative efficiencies of insect flight across the Class. Here, we use Digital Particle Image Velocimetry to measure the instantaneous downwash distribution, mid-downstroke, of a tethered desert locust (Schistocerca gregaria). By integrating the downwash distribution, we are thereby able to provide the first direct empirical measurement of k for an insect. The measured value of k = 1.12 corresponds reasonably well with that predicted by previous theoretical studies.